2020
DOI: 10.1017/s0950268820002125
|View full text |Cite
|
Sign up to set email alerts
|

Ecologic association between influenza and COVID-19 mortality rates in European countries

Abstract: Ecologic studies investigating COVID-19 mortality determinants, used to make predictions and design public health control measures, generally focused on population-based variable counterparts of individual-based risk factors. Influenza is not causally associated with COVID-19, but shares population-based determinants, such as similar incidence/mortality trends, transmission patterns, efficacy of non-pharmaceutical interventions, comorbidities and underdiagnosis. We investigated the ecologic association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
(72 reference statements)
0
17
0
Order By: Relevance
“…Petti et al 39 ecological study, including data from thirty‐four European countries, found an inverse correlation between the extent of influenza vaccination coverage and the risk of death from COVID‐19. Other authors have suggested a reduced risk of SARS‐CoV‐2 infection in subjects vaccinated with the influenza vaccine.…”
Section: Resultsmentioning
confidence: 98%
“…Petti et al 39 ecological study, including data from thirty‐four European countries, found an inverse correlation between the extent of influenza vaccination coverage and the risk of death from COVID‐19. Other authors have suggested a reduced risk of SARS‐CoV‐2 infection in subjects vaccinated with the influenza vaccine.…”
Section: Resultsmentioning
confidence: 98%
“…was correlated with the distribution of influenza mortality rates in the years 2016-2019, suggesting that in Spring 2020, SARS-CoV-2 circulation in Europe was already as sustained as the endemic influenza virus in previous years [13].…”
Section: The Distribution Of Covid-19 Mortality Rates Across European Countries In May 2020mentioning
confidence: 89%
“…Regarding our second implication, even though many of the parallels drawn between COVID-19 and influenza have already been discredited (20)(21)(22)(23)(24)(25)(26), it is often difficult to communicate this to the wider population. Our epidemiological mapping provides visually intuitive support to this difference which can help combat the misinformation that the impact of COVID-19 is no different to influenza.…”
Section: Discussionmentioning
confidence: 96%